The Effect of Tax Rates, Tax Sanctions, and Understanding of Taxation on Taxpayers' Perceptions Regarding Tax Fraud - Kabanga, Grace Otoviani; Pontoh, Grace T; Damayanti, Ratna Ayu (Contemporary Journal on Business and Accounting, 2024)
Purpose – This research aims to test and analyze the influence of tax rates, tax sanctions, and understanding of taxation on taxpayers' perceptions regarding tax fraud Design/methodology/approach – The sampling method used in this research was purposive sampling by distributing questionnaires using Google Form, with a total of 73 respondents Findings – The results of this research show that tax rates, tax sanctions, and understanding of taxation have a positive and significant effect on taxpayers' perceptions regarding tax fraud Originality – The sample used is data from MSME taxpayers registered with the Makassar City Cooperatives and SMEs Service Keywords Tax Rates, Tax Sanctions, Understanding Taxation, Tax Fraud Paper Type Research Result